Relationship between human safety and horse handling - Boross, Barbara (SLU/Dept. of Animal Environment and Health (until 231231), 2014)
This report reviews the current scientific results on the interaction between human safety and horse handling practices. It gives suggestions to and support riding instructors, riders, horse handlers and farriers how to build up a training programme which is safer for the human and safeguarding horse welfare at the same time. The discussion emphasises the common injury patterns and risk factors that need to be taken into consideration. The human-horse interaction has been looked at from the animal and the human viewpoint separately: not only the perception, learning abilities and personality of the horse but also the human comprehension and their behaviour towards the animal have been reviewed. The report gives suggestions on how these factors can be implemented in training/handling practices to reduce the injury risk of humans while horse welfare is safeguarded.